Development of a parent experience measure for paediatric critical care transport teams. Issue 3 (24th May 2021) - Evans, Ruth E. C.; Barber, Victoria; Seaton, Sarah; Draper, Elizabeth S.; Rajah, Fatemah; Pagel, Christina; Polke, Eithne; Ramnarayan, Padmanabhan; Wray, Jo; ,
Abstract: Background: A third of children admitted to paediatric intensive care units (PICUs) in the United Kingdom (UK) are transported by paediatric critical care transport services (PCCTs). Parents have described the transfer journey as particularly stressful. Critical care nurses have a key role in mitigating the impact of the journey on parents. Evaluating parents' experiences is important to inform service improvements. Aim and objectives: Our aim was to describe the development of a new measure of parents' experiences of PCCTs, derived from data collected in the Differences in access to Emergency Paediatric Intensive Care and care during Transport (DEPICT) study. Design: A descriptive cross‐sectional survey was used. Methods: As part of the DEPICT study, a 17‐item transport experience questionnaire was developed and given to parents of children transported by PCCTs to 24 UK PICUs during a 12‐month period. Analyses included exploratory factor analysis and a validation review by a PCCT stakeholder group. Results: Families of 1722 children (1798 journeys) completed questionnaires. Five items were excluded from further analysis as correlation coefficients were <0.3. Two factors explained 53% of the variance and all 12 items loaded on one of these factors. Factor 1 (8 items) explained 47% of the variance, had excellent internal reliability and the clustered items were conceptually coherent with a specific relevance to PCCTs; these were offered for consideration, with other items possibly discarded. Twenty‐eight PCCT clinicians reviewed the questions. Using a 70% agreement threshold, one additional, previously discarded, item was identified for inclusion, resulting in a nine‐item experience measure. Conclusion: Our brief measure of parents' experience of critical care transport provides a standardized measure that can be used across all PCCTs, enabling national benchmarking of services and potentially increasing the collection and use of parent experience data to improve services. Relevance to clinical practice: Being able to measure experience provides an opportunity to understand how to make services better to improve experience.